A Note on Two Abnormal Seedlings from Pinus caribaea Var. Hondurensis and P. Oocarpa - Kandya, A. K. (Indian Forester, 1979)
Two abnormal seedlings, One of Pinus caribaea Morelet var hondurensis proveanance 43/71 and the Other of P. oocarpa Sahiede Proverance 9/70 were obaerved during a study of seed and sedling characteristics of various provenances or these species in relation to their geographical parameters Aboormalities Were similar in both the seedlings and several possible hypotbetical explanations Have been given in this note for these abnormalities.